IMPROVING THE TIME OF DISCHARGE BASED ON LEAN SIX SIGMA: AN ANALYSIS AND RECOMMENDATION - Kinanti Setyastuti; Dyah Yuniati; Djazuly Chalidyanto (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
The patient discharge process at Jemursari Islamic Hospital, Surabaya for the four types of patient insurance, namely BPJS, General, Institution, and Private Insurance, does not currently meet the standard operating procedures of a 2-hour discharge time. This study was observational using a quantitative analysis approach with the Six Sigma methodology. The study measured the time variation and sigma level of each process and sub-process. Qualitative analysis was conducted through a Focus Group Discussion to identify activities. The sample size was 100 respondents, including 70 patients with BPJS insurance, 10 patients with general insurance, 8 patients with institutional insurance, and 12 patients with private insurance. The findings showed that the average total time for the patient discharge process was 166.61 minutes for patients with BPJS insurance, 252.60 minutes for patients with general insurance, 258.16 minutes for patients with institutional insurance, and 229.69 minutes for patients with private insurance. The sigma level of the sub-processes for discharging inpatient patients guaranteed by BPJS was near the standard level in two sub-processes. The sigma level of the sub-processes for discharging inpatient patients with general and institutional insurance in inpatient care was near the standard level. The sigma level of the sub-processes for discharging inpatient patients with private insurance was near the standard level in one sub-process.